Genome Re-Sequencing Reveals the Host-Specific Origin of Genetic Variation in Magnaporthe Species - Li, Jinbin; Lu, Lin; Wang, Qun; Shi, Zhufeng; Li, Chengyun; Guo, Zhixiang (Frontiers in Genetics, 2022)
Rice blast is caused by Magnaporthe oryzae (M. oryzae), which is considered one of the most serious pathogens of rice around the globe. It causes severe losses owing to its proven capability to disrupt the host resistance. Recently, its invasion of new hosts like the Musa species or banana plants has been noticed. To understand the possible level of genetic variation, we sequenced the genomes of eight different isolates of the Magnaporthe species infecting rice, Digitaria (a weed), finger millet, Elusine indica, and banana plants. Comparative genomic analysis of these eight isolates with the previously well-characterized laboratory strain M. oryzae 70-15 was made. The infectivity of the newly isolated strain from Musa species suggested that there is no resistance level in the host plants. The sequence analysis revealed that despite genome similarities, both the banana and Digitaria isolates have relatively larger genome sizes (∼38.2 and 51.1 Mb, respectively) compared to those of the laboratory reference strain M. oryzae 70-15 (∼37 Mb). The gene contraction, expansion, and InDel analysis revealed that during evolution, a higher number of gene insertions and deletions occurred in the blast fungus infecting Digitaria and banana. Furthermore, each genome shared thousands of genes, which suggest their common evolution. Overall, our analysis indicates that higher levels of genes insertion or deletions and gain in the total genome size are important factors in disrupting the host immunity and change in host selection.